Nitrogen management and ground water protection - Follett, R. F. (Ronald F.), 1939- (Developments in agricultural and managed-forest ecology, 1989)
Supplying crops with adequate nitrogen is vital to ensuring food supplies. Once nitrogen is added to the soil, it is subject to chemical transformations of the nitrogen-cycle including transformation to nitrate. Excessive amounts of accumulated nitrate may then leach out of the soil and could potentially enter and contaminate drinking water supplies. The purpose of this book is to examine the subject of nitrogen management and ground water protection. The issue of maintaining ground water quality is addressed primarily from an agronomic point of view. Topics covered include: health and economic aspects of nitrate in drinking water; nitrate sources; ground water nitrate in the USA and other developed countries; transport, leaching and accounting for nitrogen; soil, nitrogen, crop and water management; and nitrate in aquifer systems. The book contains a keyword index and is organized into thirteen chapters, each with appropriate references, tables and figures. Chapter authors are among the leading experts on the subject of nitrate and ground water quality. Readers to whom the book is directed include soil scientists and agronomists, agricultural engineers (irrigation and drainage), environmental scientists, agricultural policy makers, and hydrologists.